2012
DOI: 10.1371/journal.pone.0030582
|View full text |Cite
|
Sign up to set email alerts
|

Sources of Dietary Protein in Relation to Blood Pressure in a General Dutch Population

Abstract: BackgroundLittle is known about the relation of different dietary protein types with blood pressure (BP). We examined whether intake of total, plant, animal, dairy, meat, and grain protein was related to BP in a cross sectional cohort of 20,820 Dutch adults, aged 20–65 y and not using antihypertensive medication.DesignMean BP levels were calculated in quintiles of energy-adjusted protein with adjustment for age, sex, BMI, education, smoking, and intake of energy, alcohol, and other nutrients including protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 27 publications
2
23
2
Order By: Relevance
“…Both SBP and DBPs were lower in subjects who consumed ≥2.5 g soy food compared with subjects who consumed <2.5 g.[ 24 ] In addition, PREMIER, INTERMAP studies and another study with cross-sectional design showed an inverse relationship between plant protein consumption and HTN risk, while animal and total protein intake had no significant association with BP. [ 10 25 26 ] Furthermore, consistent to our results, a meta-analyses study based on the findings from forty randomized-controlled trials (RCTs) demonstrated that the higher consumption of all sources of protein was associated with lower BP in healthy subjects. [ 27 ] In addition, a systematic review of 46 studies found a weak inverse association between total protein intake and BP among hypertensive participants.…”
Section: Discussionsupporting
confidence: 86%
“…Both SBP and DBPs were lower in subjects who consumed ≥2.5 g soy food compared with subjects who consumed <2.5 g.[ 24 ] In addition, PREMIER, INTERMAP studies and another study with cross-sectional design showed an inverse relationship between plant protein consumption and HTN risk, while animal and total protein intake had no significant association with BP. [ 10 25 26 ] Furthermore, consistent to our results, a meta-analyses study based on the findings from forty randomized-controlled trials (RCTs) demonstrated that the higher consumption of all sources of protein was associated with lower BP in healthy subjects. [ 27 ] In addition, a systematic review of 46 studies found a weak inverse association between total protein intake and BP among hypertensive participants.…”
Section: Discussionsupporting
confidence: 86%
“…Because of the strong interrelations previously reported between blood pressure and protein source, and because we observed a significant interaction in the current analyses, we further examined the relation between amino acid intake and arterial stiffness according to protein source. Protein from vegetable sources, but not animal sources, has previously been shown to be associated with a −1.1 mm Hg reduction in pSBP and 15% reduction in risk of hypertension ( 3 , 4 ). We found that higher intakes of amino acids from vegetable sources, but not animal sources, were associated with lower systolic blood pressure, MAP, and AI.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a meta-analysis of 40 randomized, controlled trials reported significant decreases in blood pressure with increased intakes of total (systolic −1.8 mm Hg and diastolic −1.2 mm Hg), animal (systolic −2.5 mm Hg and diastolic −1.0 mm Hg), and vegetable (systolic −2.3 mm Hg and diastolic −1.3 mm Hg) protein ( 2 ). Other studies, however, have found that it is protein from vegetable sources that is inversely related to blood pressure, with no significant effects for animal protein ( 3 , 4 ). Furthermore, plant protein has been shown to be a strong marker of dietary quality, whereas the findings for animal protein are currently equivocal ( 5 ).…”
Section: Introductionmentioning
confidence: 89%
“…A report of two cohort studies found that a low‐carbohydrate diet based on animal sources was associated with higher all‐cause mortality, while a vegetable‐based low‐carbohydrate diet was associated with lower all‐cause and cardiovascular disease mortality rates 26 . Other studies have shown benefits of plant protein compared with animal protein for lowering blood pressure 27 , 28 and the risk of type 2 diabetes 29 , 30 and of ischaemic heart disease in healthy men 31 . Furthermore, consumption of soy protein may slow the progression of kidney disease compared with consumption of animal protein, particularly red meat 32…”
Section: The Benefits Of Plant Proteinmentioning
confidence: 99%